The Crystal Structure and Physicochemical Properties of New Complexes Containing a CuII-LnIII-CuII Core - Beata Cristóvão; Dariusz Osypiuk; Barbara Mirosław (Crystals, 2024)
Three new cationic complexes, [Cu4Tb2(H2L)4(NO3)4(H2O)3](NO3)2·5.5H2O·2MeOH (1), [Cu4Ho2(H2L)4(NO3)4(H2O)3](NO3)2·7.5H2O (2), and [Cu4Er2(H2 L)4(NO3)4(H2O)3](NO3)2·7H2O·3MeOH (3), were synthesized and studied using elemental and TG/DTG/DSC analyses, single-crystal X-ray diffraction, and magnetic measurements. The structure analysis showed that 1–3 crystallize as (NO3)-bridged compounds and that the lanthanide(III) ion acts as a joint connecting two [CuH2L] coordination units. In each heterotrinuclear unit, an asymmetry in the degree of planarity of the bridging CuO2Ln fragments is observed. The CuII ions are five- and six-coordinate, with distorted square pyramidal and octahedral geometry, respectively, whereas the LnIII ions are nine-coordinate. The solvates 1–3 are stable at room temperature, and their desolvation process is consistent with the loss of water and/or methanol molecules. The temperature dependence of the magnetic susceptibility and the field-dependent magnetization indicate the weak ferromagnetic interaction between the paramagnetic centers CuII and TbIII/HoIII 1 and 2.